2012
DOI: 10.1016/j.ijgo.2012.01.015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of emergency obstetric care training in Somaliland, Somalia

Abstract: The training impacted positively on the availability and quality of EmOC and resulted in "up-skilling" of midwives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 17 publications
7
87
0
1
Order By: Relevance
“…Thirteen studies had been conducted in [19][20][21][22][23][24][25][26][27][28] 6 DH (L2&L3) -HIC 10 RCT 2a,b,c 3b NHS Foundation Trust, Liverpool, UK [44,45] --HIC 1 Before-after 4b,c Victoria, Australia [46] 7 [48] --LMIC 1 Before-after 1 2b −−− −−− Sub-Saharan Africa (7 countries) [49] --LMIC 1 Before-after 1 2b,c −−− −−− Somaliland, Somalia [50] 3 8 LMIC 1 Before-after 1 2b,c 3a 4b Making it Happen, Bangladesh & India [52] 4 DH (Bangl.) [54] 3 DH; 3 FH 40 LMIC 1 Quasi-experimental 3c CRM based National study, US [58] 15 -HIC 1 RCT 4c Beth Israel Deaconness Medical Center, US [59] 1 TTH -HIC 1 Before-after 2a 4b,c Perinatal Safety Initiative, US [60] 1 TH -HIC 1 Before-after 3a 4b,c Rhode Island Hospital, US [61] 1 -HIC 1 Before-after 4b,c Geneva University Hospital, Switzerland [63] 1 TTH -HIC 1 Before-after 1 2a 3a TeamSTEPPS, US [18] 3 CH -HIC 1 RCT 2a 4c OBCTT, Southeast US [62] 1 TTH -HIC 1 Quasi-experimental before-after 1 2a,b,c −−− −−− OTHER CEmONC, Tanzania [17] 1 DH LMIC 1 Before-after 3c Copenhagen University Hospital, Denmark [64] 1 TTH -HIC 1 Before-after 1 2a,b 3a 4b University of Oporto, Portugal [65] 1 TTH -HIC 1 Before-after 1 2b 3a * In progress -abstracts not included [31,32] DH = district hospital L1 = level 1 −−− = studies not going beyond Kirkpatrick level 2 RH = referral hospital L2 = level 2 (secondary/regional) FH = field hospital TH = tertiary hospital/medical centre L3 = level 3 (tertiary) CH = community hospital TTH = tertiary and teaching hospital included in the studies spans the whole spectrum from tertiary teaching hospitals to community-and field hospitals.…”
Section: Synopsis Of Peer-reviewed Articles Included In the Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen studies had been conducted in [19][20][21][22][23][24][25][26][27][28] 6 DH (L2&L3) -HIC 10 RCT 2a,b,c 3b NHS Foundation Trust, Liverpool, UK [44,45] --HIC 1 Before-after 4b,c Victoria, Australia [46] 7 [48] --LMIC 1 Before-after 1 2b −−− −−− Sub-Saharan Africa (7 countries) [49] --LMIC 1 Before-after 1 2b,c −−− −−− Somaliland, Somalia [50] 3 8 LMIC 1 Before-after 1 2b,c 3a 4b Making it Happen, Bangladesh & India [52] 4 DH (Bangl.) [54] 3 DH; 3 FH 40 LMIC 1 Quasi-experimental 3c CRM based National study, US [58] 15 -HIC 1 RCT 4c Beth Israel Deaconness Medical Center, US [59] 1 TTH -HIC 1 Before-after 2a 4b,c Perinatal Safety Initiative, US [60] 1 TH -HIC 1 Before-after 3a 4b,c Rhode Island Hospital, US [61] 1 -HIC 1 Before-after 4b,c Geneva University Hospital, Switzerland [63] 1 TTH -HIC 1 Before-after 1 2a 3a TeamSTEPPS, US [18] 3 CH -HIC 1 RCT 2a 4c OBCTT, Southeast US [62] 1 TTH -HIC 1 Quasi-experimental before-after 1 2a,b,c −−− −−− OTHER CEmONC, Tanzania [17] 1 DH LMIC 1 Before-after 3c Copenhagen University Hospital, Denmark [64] 1 TTH -HIC 1 Before-after 1 2a,b 3a 4b University of Oporto, Portugal [65] 1 TTH -HIC 1 Before-after 1 2b 3a * In progress -abstracts not included [31,32] DH = district hospital L1 = level 1 −−− = studies not going beyond Kirkpatrick level 2 RH = referral hospital L2 = level 2 (secondary/regional) FH = field hospital TH = tertiary hospital/medical centre L3 = level 3 (tertiary) CH = community hospital TTH = tertiary and teaching hospital included in the studies spans the whole spectrum from tertiary teaching hospitals to community-and field hospitals.…”
Section: Synopsis Of Peer-reviewed Articles Included In the Reviewmentioning
confidence: 99%
“…A number of studies in the literature reviewed indicated how their authors had evaluated their own programmes according to the four levels of training achievements described by Kirkpatrick [11,14,19,50,63,64,68,76]. The first two levels refer to the reaction of training participants (satisfaction after training) and the knowledge and skills learning of the trainee.…”
Section: The Kirkpatrick Classification Of Evaluating Training Programmementioning
confidence: 99%
See 1 more Smart Citation
“…[28] These study findings concur with the results of previous research on similar CPD education programs which reported increased knowledge, skills, and confidence among participants in obstetric emergency management. [28,29] The midwives perceived that maternal deaths decreased after having participated in an ALSO R course. Participants' perceptions of the reduction of maternal deaths might be attributed to their improved ability to prevent and manage PPH, avoidance of performing unnecessary episiotomies, and improved inter-professional team work.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were demonstrated in a study conducted in Somalia to assess the impact of in-service education programs on emergency obstetric care, where 90% of participants were nurses and midwives The findings showed that lack of drugs, materials and essential equipment, and discouraging policies were barriers which hampered the translation of new knowledge and skills acquired into practice. [29] In the field of maternal and newborn health services, the shortage of skilled birth attendants and limited materials and equipment are critical barriers to availability of quality emergency obstetric care in low and middle resource countries. [30,31] Inadequate implementation of evidence-based interventions to reduce maternal and newborn mortality in limited resource settings is primarily due to lack of resources.…”
Section: Discussionmentioning
confidence: 99%